(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
دلت نتائج الدراسة وجود تراجع معدل إنتاجية شجرة الكرمة في حلب وحمص والسويداء بلغ على التوالي (2.0808 - ، 0.1071 - ، 2.488 - ) وتزايد في حماه بلغ (0.3648) كغ/ شجرة . تفاوتت التراكمات الحرارية الفعالة خلال موسم نمو الكرمة في كل منطقة من المناطق الأربع وبقيم بلغت (2863.6 ، 2793.8 ، 2539.8 ، 2212.4 درجة نمو يومية) في حماه ، حلب ، حمص ،السويداء على التوالي. أيضاً وضحت نتائج معادلات اتجاه التغير (الترند) وجود زيادة في التراكمات الحرارية الفعالة خلال موسم نمو العنب في حلب وحماه وحمص وتراجع في السويداء . أخيراً ربطت معادلات الانحدار المتعدد بين إنتاجية الكرمة وأهم أربع عناصر مناخية مؤثرة خلال مراحل نمو العنب في كل منطقة من المناطق الأربع المدروسة . The results of this study clearly indicate that the average of vitis vinifera productivity has decreased during the research period in Aleppo, Homs, and Sweida by (-2.0808,-0.1071,-2.488 kg/tree), respectively , and has increased in Hama by (0.3648 kg/tree). The effective thermal accumulation during the growing season of vitis vinifera in each area reaches ( 2863.6,2793.8,2539.8,2212.4 G.D.D.) in Hama, Aleppo, Homs and Sweida, respectively. The results of Trend have demonstrated an increase in the effective thermal accumulations during growing season of the grapes in Aleppo, Hama, and Homs, and a decrease in Sweida. Finally, the multi-slope equation has attributed the productivity of grapes to the four most important climatic conditions affecting grapes during the growing stages in each of the four areas.